Perceived Discrimination Difference between the Manjo Minority and Non-Manjo Ethnic Group in Kaffa Zone, Ethiopia (Research, Society and Development, 2020)
This study has attempted to examine perceived discrimination difference between the Manjo clan and non-manjos in Kaffa zone that is located in the south west of Ethiopia. A total of 298 individuals who belong to the manjo and non-manjo groups were randomly selected and involved in the study. The researchers utilized an independent sample t-test to compare the level of perceived discrimination between the Manjo and the non-Manjos ethnic groups. Seen segregation is the changeability of thought coming because of behavior of isolating group of people that radiates from predisposition and partiality. As revealed in the study, there is a significant mean variation among manjos and non-manjos with respect to perceiving discrimination. The thought of being discriminated showed significant mean difference between the group of manjos and non-manjos. The finding implies the need for further research and social work intervention to minimize the action and sense of being discriminated as this relates to the overall psychosocial wellbeing of persons in a given community.